PENGARUH PERUBAHAN TARIF PAJAK IMPOR ATAS PEMBERLAKUAN PMK.199/PMK.010/2019, PENETAPAN HARMONIZED SYSTEM, DAN PREFERENSI BELANJA SETELAH PERUBAHAN DE MINIMIS THRESHOLD TERHADAP KEPUTUSAN PEMBELIAN IMPORTIR - Merlin Fitri Qhairunisa; Rulyanti Susi Wardhani; Vebtasvili Vebtasvili (LPPM Institut Pendidikan Nusantara Global, 2023)
Merlin Fitri Qhairunisa. 301 19 11 047. 2023. In recent years, the volume of imports of goods has increased significantly due to the sale of imported goods by e-commerce actors in importing goods, to reduce the volume of imported goods, the government has imposed new rules regarding the import of consignments, regulated in PMK 199/PMK 010/ 2019 concerning Customs, Excise and Tax Provisions on Imported Goods. This study aims to analyze the effect of changes in tax rates, establishment of a harmonized system, and shopping preferences on importers' decisions in purchasing imported e-commerce goods. This research approach is a quantitative descriptive analysis with a sample of 105 respondents. The sampling technique uses a non-probability sampling technique using a purposive sampling method. Based on the research results, changes in import tax rates, harmonized systems and shopping preferences have a positive and significant effect on importers' purchasing decisions. The results of this study are expected to provide information as a basis for consideration, support, and contribution of ideas to importers and the government in an effort to reduce import volumes and reduce the trade balance deficit.